Empowering mass spectrometry & separation sciences for clinical laboratory - Akmal, Fakhril (Indonesian Nutrition Association, 2024)
Mass spectrometry (MS) has been a gold standard in the clinical laboratory for decades. Although historically refined to limited areas of study such as neonatal screening and steroid analysis, technological advancements in the field have resulted in MS becoming more powerful, versatile, and user-friendly than ever before.